Immunotherapy for Metastatic Melanoma with Right Atrial Involvement in a Patient with Rheumatoid Arthritis. (28th December 2017) - Benson, Zachary; Gordon, Sarah; Nicolato, Patricia; Poklepovic, Andrew
Abstract : Prognosis for metastatic melanoma has improved significantly with the use of immune checkpoint inhibitors. Given improvements in survival, aggressive surgical treatment may be considered in patients with life-threatening complications from their disease that would not otherwise be considered in advanced disease. Patients with preexisting autoimmune diseases or prior immune-related adverse events from therapy are largely excluded from clinical trials. Concerns exist that immunotherapy in these patients could worsen autoimmune disease or increase the risk of developing additional immune-related adverse events on therapy. We present a case of a patient with rheumatoid arthritis that presented with obstructive heart failure secondary to melanoma that had metastasized to the right atrium. After aggressive surgical resection to stabilize him from his life-threatening heart failure, he was treated with ipilimumab, which was stopped due to an immune-related adverse event. He was then started on pembrolizumab and had a durable response to therapy. Aggressive surgical treatment should be considered in patients with a cancer that may respond to immunotherapy. Furthermore, some patients with preexisting autoimmune disease may be safely treated with checkpoint inhibition therapy, and patients with a severe immune toxicity from one class may successfully be treated with an alternate class.